2019
DOI: 10.1177/0007650319847477
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Female Directors in the Boardroom: Examining Their Impact on Competitive Dynamics

Abstract: This study contributes simultaneously to research on women board members and competitive dynamics by investigating two unresolved research questions: What is the effect of female directors on the firm’s competitive repertoire? Under what conditions is this effect more pronounced? Leveraging the “Awareness-Motivation-Capability” (AMC) framework, we predict that having women on the board of directors should impact the complexity, heterogeneity, and volume of the firm’s competitive moves. Relying upon a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 125 publications
(209 reference statements)
0
12
0
Order By: Relevance
“…Recent articles in this journal also explored the women directors and financial performance linkages. Women board of directors influenced positively the complexity and volume of competitive moves (Kolev et al, 2019), though negatively on the heterogeneity of competitive actions.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent articles in this journal also explored the women directors and financial performance linkages. Women board of directors influenced positively the complexity and volume of competitive moves (Kolev et al, 2019), though negatively on the heterogeneity of competitive actions.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Cabrera-Fernández et al (2016) examined 76 studies that looked at women's contribution to firm profitability, establishing the 'business case' for having more women on boards. Research reported the linkage as mixed (Kolev, Hughes-Morgan, & Rehbein, 2019;Wagana & Nzulwa, 2016). Kang and Payal (2012) reviewed several studies which indicated positive effects of having women on boards, while other studies also showed negative findings (Abdullah, Ismail, & Nachum, 2016;Ahern & Dittmar, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, beyond the fact that having a diverse workforce is a moral imperative for corporations, the many recent corporate governance scandals have drawn attention to the issue of board composition, and how ensuring demographic diversity in board composition may have prevented these. Other than moves by regulatory bodies such as the California legislature and Securities and Exchange Commission to facilitate more gender diversity on corporate boards (Kolev, Hughes-Morgan, & Rehbein, 2021a), shareholder activists—such as large institutional investors, including State Street Global Advisors, the New York Pension Funds, and BlackRock, amongst others—have made it a priority to increase female board representation by filing shareholder resolutions and exercising their voting rights against members of underrepresented boards (Kolev et al, 2021b; Ross-Sorkin, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The selection of a board director is an important topic in corporate governance research because directors have an important impact on firm performance through their monitoring and advising roles (Adams, Hermalin, & Weisbach, 2010; Carpenter, Geletkanycz, & Sanders, 2004; Kumar & Sivaramakrishnan, 2008). At the moment, however, many studies have documented an underrepresentation of female directors within boards (Daily, Certo, & Dalton, 1999; Terjesen, Sealy, & Singh, 2009) and concurrent efforts to increase diversity (Kolev, Hughes-Morgan, & Rehbein, 2021b; Terjesen et al, 2009). For example, recent regulatory initiatives to improve this include California’s 2018 Women on Boards Bill to advance equitable gender representation on California corporate boards (Weber, 2018), as well as Nasdaq’s Board Diversity Rule approved by the Securities and Exchange Commission on August 6, 2021 (Gibson Dunn, 2021).…”
mentioning
confidence: 99%
“… 1 Scholars examining other types of effects of board gender diversity on organizations have similarly shifted their focus away from analyzing the direct impact on indicators of firm outcomes toward identifying specific actions through which female directors affect these outcomes (Kolev et al, 2021). …”
mentioning
confidence: 99%